Latin America and the Asian giants : evolving ties with China and India - Roett, Riordan, 1938-; Paz, Guadalupe, 1970-; Kahn, Theodore (Brookings Institution Press, 2016)
"How an evolving relationship with China and India is changing Latin America's political and economic dynamics. In the years since China has adopted a "going global" strategy to promote its overseas investment, expand export markets, and gain much-needed access to natural resources abroad, Sino-Latin American relations have both deepened and broadened at an unexpectedly rapid pace. The main driver behind this sea change in bilateral relations has been economic complementarity, with resource-rich countries in Latin America exporting primary goods to the Asian giants' growing market and China exporting manufactured goods back into the region. In recent years, Sino-Latin American relations have matured considerably, becoming far more nuanced and multifaceted than ever before. India is a relatively new player in the region, but has slowly strengthened its ties. As one of Asia's largest markets, it offers interesting parallels to the Chinese case. Will Indo-Latin American ties follow a similar path? The main areas of growth include trade and investment, mining, energy, information technology, motor vehicle production, and pharmaceuticals. To what extent these changing dynamics will redefine Latin America's relations with India is a question of increasing relevance for policymakers. This volume offers a review of key cross-regional trends and critical policy issues involving the changing relationship between these two Asian giants and Latin America. Selected country case studies-Argentina, Brazil, Chile, and Mexico-provide a more in-depth analysisof the implications of China's and India's evolving interaction with the region"--